INVESTIGATING THE IMPACT OF TECHNOLOGICAL ADVANCEMENTS ON LABOR PRODUCTIVITY IN THE MANUFACTURING SECTOR OF INDIA - Singh, Ayushi; Singh, Aakanksha; Khanduja, Bhavya; Mishra, Rahul; Kumar, Vikas (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Objective/Aim: This study aims to determine the effects of technological change on Labor Productivity (LP) in the manufacturing sector of India, with particular emphasis on Automation Technology (AT), Digitalization (DT), and Skill Development (SD). This study seeks to understand the influence of technological factors on labor productivity and their interrelations. Methodology/Approach: A cross-sectional research study is used with online survey data collection. From October 2023 toMarch 2024, 407 professionals in the manufacturing sector are taken into consideration. Data isanalyzed by using the software SPSS. For all of the dependent relationships, which are H1, H2, and H3, multiple linear regression tests is conducted, and Pearson's correlation is applied on independent relationships H4, H5, and H6. Findings: It gives insight into how the independent variables of Automation Technology, Digitalization, and Skill Development impact Labor Productivity in India's manufacturing sector. It also calculates the strength and direction of correlations between these independent variables. This study is novel in the approach taken for the examination of the compounded effects of automation, digitalization, and skill building on labor productivity, in the Indian manufacturing context specifically. Limitations and Recommendations: The limitations of the research include convenience sampling, which causes bias, and the data derived from self-reported measures in the respondents. For the future, it could provide a larger sample with broader diversity or a longitudinal study tracking changes over time. Organizations are advised to invest in automating, digitalization of tools, and workforce training for efficiency in labor productivity.